2018
DOI: 10.1080/23322039.2018.1432450
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic indicators and their impact on stock markets in ASIAN 3: A pooled mean group approach

Abstract: The objective of this paper is to examine the long-run and the short-run relationship between India, China and Japanese stock markets and key macroeconomic variables such as exchange rates and inflation (proxied by consumer price index) of ASIAN 3 economies (India, China and Japan). Monthly time series data spanning the period from 2008 January to November 2016 has been used. The unit root test, the cointegration test, Granger causality test and pooled mean group estimator have been applied to derive the long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
3
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 25 publications
2
42
3
2
Order By: Relevance
“…Thus, Ho 4 is accepted and the alternative suggestion which states otherwise rejected. However, this finding is not consistent with the findings of (Khodaparasti, 2014;Nijam, et al, 2015;Giri & Joshi, 2017;Golam et al, 2017;Khalid & Khan, 2017;Epaphra & Salema, 2018;Megaravalli & Sampagnaro, 2018) who found in their studies that exchange rate significantly and positively influenced stock market performance. The result also contradicts the findings of Khan and Khan (2018) whose study revealed that exchange rate influenced stock prices of Karachi Stock Exchange in Pakistan significantly and negatively in the short run.…”
Section: Test Of Hypothesiscontrasting
confidence: 65%
See 1 more Smart Citation
“…Thus, Ho 4 is accepted and the alternative suggestion which states otherwise rejected. However, this finding is not consistent with the findings of (Khodaparasti, 2014;Nijam, et al, 2015;Giri & Joshi, 2017;Golam et al, 2017;Khalid & Khan, 2017;Epaphra & Salema, 2018;Megaravalli & Sampagnaro, 2018) who found in their studies that exchange rate significantly and positively influenced stock market performance. The result also contradicts the findings of Khan and Khan (2018) whose study revealed that exchange rate influenced stock prices of Karachi Stock Exchange in Pakistan significantly and negatively in the short run.…”
Section: Test Of Hypothesiscontrasting
confidence: 65%
“…The findings revealed that FDI, savings, economic growth, trade openness, exchange rates, banking sector development and stock market liquidity affected the development of the emerging nations' stock market positively and substantially. In a similar study, Megaravalli and Sampagnaro (2018) inspected the long run and short run effect of macroeconomic pointers on financial exchanges in ASIAN 3 economies which include: China, India and Japan utilizing month to month time arrangement information from 2008 to 2016. The examination discovered proof that swapping scale had a huge positive effect on the securities exchanges over the long haul while swelling had an immaterial negative effect on the financial exchanges.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Thus, Ho1 is accepted and the alternative suggestion which states otherwise rejected. However, this finding is not consistent with the findings of (Khodaparasti, 2014;Nijam, et al, 2015;Giri & Joshi, 2017;Golam et al, 2017;Khalid & Khan, 2017;Epaphra & Salema, 2018;Megaravalli & Sampagnaro, 2018) who found in their studies that exchange rate significantly and positively influenced stock market performance. The result also contradicts the findings of Khan and Khan (2018) whose study revealed that exchange rate influenced stock prices of Karachi Stock Exchange in Pakistan significantly and negatively in the short run.…”
Section: Model Specificationcontrasting
confidence: 65%
“…The study also established the existence of a long run relationship between macroeconomic fundamentals and stock market performance. Megaravalli and Sampagnaro (2018) examined the long run and short run impact of macroeconomic indicators on stock markets in ASIAN 3 economies which include: China, India and Japan using monthly time series data from 2008 to 2016. The study found evidence that exchange rate had a significant positive impact on the stock markets in the long run while inflation had an insignificant negative impact on the stock markets.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The result is a large body of literature that provides evidence on how macroeconomic fundamentals and financial markets are connected. Under the weak form of the efficient capital markets theorem, researchers at first considered the impact of macroeconomic indicators on the prices of exchange-traded stocks (Megaravalli & Sampagnaro, 2018;Lee & Wang, 2015;Pilinkus, 2010), but a few other researchers tested for the existence of a causal influence of macroeconomic indexes on stock prices (Plihal, 2016). Researchers have also looked at how to explain market anomalies by conducting volatility tests, such as seasonality or a disproportionate frequency of stock returns (Flannery & Protopapadakis, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%